(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2018)
Introduction: There are some reports where serum lead levels were measured and change in concentration of serum lead level was found among Acute Lymphoblastic Leukemia patients. The aim of this study was to determine serum lead levels in patients with ALL. Methods: In this cross sectional study all children suffering from acute lymphoblastic leukemia ranging 2 to 12 years (30 patients) were evaluated for serum lead levels who were admitted at the Department of Pediatrics in DMCH, from February 2013 to January 2014. Serum measurements for lead were performed by Atomic absorption spectrophotometer in Analytical Chemistry Laboratory of Atomic Energy Centre Ramna, Dhaka. Results: Among the 63 children there was no significant difference in age and sex between the patients and control. The mean serum lead level of Acute lymphoblastic Leukemia patient group (234.8±162.9 g/L) was significantly higher than that of the control group (23.6±12.6 µg/L). There was significant difference of serum lead level in children with ALL and control group(p<0.05). Conclusion: From the findings of the study it can be concluded that there is significant difference between Acute Lymphoblastic Leukemia patient and normal control in terms of serum Lead (pb) level. Key words: Children, Acute Lymphoblastic Leukemia, serum Lead. Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (2): 41-45